KADAR KALSIUM DAN FOSFOR DALAM DARAH SAPI PERAH DI DAERAH PAKEM DAN KEBUN PENDIDIKAN PENELITIAN DAN PENGEMBANGAN PERTANIAN UGM - , RIRIS DIAN WE WAHYU; , Dr.drh. Soedarmanto Indarjulianto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Improper feed management is one of the cause of hypocalcemia that will lead Cow Down Syndrome. Macromineral supplementation in proper level is needed to achieve a balance physiologic function of the diary cattle. This study was conducted to evaluate calcium and phosphorus of 17 dairy cattle in Pakem, Sleman and 17 dairy cattle in KP4 UGM. A lot of 5 ml blood samples were taken from jugular vein. Blood samples were centifugated 8000 rpm for 10 minutes, then the calcium and phosphorus levels were analyzed using Cobas c-501. The results of calcium level for dairy cattle in Pakem is 8,92 ± 1,28 mg/dl and and the phosphorus is 6,5 ± 2,02 mg/dl. The samples from KP4 UGM dairy cattle calcium level is 9,26 ± 0,54 while phosphorus is 6,96 ± 0.89. Statistic analytical using t-test independent showed that there were no significant differences of calcium and phosphorus levels between the samples from Pakem and KP4 UGM. The ratio for calcium and phosphorus from Pakem dairy cattle is 1,3 : 1 and from the KP4 UGM is 1,4 :1 The conclusion based on this study is the calcium and phosphorus levels of dairy cattle in KP4 and Pakem still in normal range.